2020
DOI: 10.1016/j.psym.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacology of COVID-19

Abstract: Background: With the rapid, global spread of severe acute respiratory syndrome coronavirus 2, hospitals have become inundated with patients suffering from coronavirus disease 2019. Consultation-liaison psychiatrists are actively involved in managing these patients and should familiarize themselves with how the virus and its proposed treatments can affect psychotropic management. The only Food and Drug Administrationapproved drug to treat COVID-19 is remdesivir, and other off-label medications used include chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 68 publications
0
98
1
3
Order By: Relevance
“…Other comorbidities were also found in these individuals, often with older age (on average 77.4 years), being more frequent among women (60%): hypertension (60%), dyslipidemia (52.5%) and diabetes (30%). It is also seen that the involvement of SARS-CoV-2 with neurological aspects can affect different levels of the Central and Peripheral Nervous System, in addition to causing skeletal-muscular injury, representing 36.4% of the cases considered, including impairment of consciousness, ataxia, acute cerebrovascular disease, seizure and neuropathic pain, for example ( Bilbul et al, 2020 ). In an epidemiologically deeper approach, Dinakaran et al (2020) reinforces a percentage value close to the one reported by Bilbul et al (2020) regarding the neurological complaints of COVID-19 patients: 36%.…”
Section: Disorders and Epidemiological Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other comorbidities were also found in these individuals, often with older age (on average 77.4 years), being more frequent among women (60%): hypertension (60%), dyslipidemia (52.5%) and diabetes (30%). It is also seen that the involvement of SARS-CoV-2 with neurological aspects can affect different levels of the Central and Peripheral Nervous System, in addition to causing skeletal-muscular injury, representing 36.4% of the cases considered, including impairment of consciousness, ataxia, acute cerebrovascular disease, seizure and neuropathic pain, for example ( Bilbul et al, 2020 ). In an epidemiologically deeper approach, Dinakaran et al (2020) reinforces a percentage value close to the one reported by Bilbul et al (2020) regarding the neurological complaints of COVID-19 patients: 36%.…”
Section: Disorders and Epidemiological Profilesmentioning
confidence: 99%
“…Associated with multiple impairments on the individual's mental and physical health, both in their psychiatric and neurological consequences, the action of SARS-CoV-2 and the immune response of the human Central Nervous System have been the focus of pathophysiological investigation ( Troyer et al, 2020 ). In this light, the neuroinvasive character of the virus in question and the manifestations at central and peripheral levels suffered by the referred system are raised: headache, dizziness - most common-, reduced level of consciousness, ataxia, impaired perception of taste and smell and neuropathic pain, possibly including also injury of skeletal muscle tissue ( Bilbul et al, 2020 ; Zhou et al, 2020 ). According to research by Beach et al (2020) the emergence of this panorama, including acute encephalopathy, can reach more than a third of patients with COVID-19, in addition to delirium as a common phenomenon of the most serious infections.…”
Section: Physiopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the start of coronavirus disease 2019 “COVID-19” pandemic, multiple treatment regimens have been tried under the compassionate use indications. So far, no specific antiviral drug has been proven to be effective, apart from remdesivir which showed promising results and has gained an emergency approval by Food and Drug Administration (FDA) to be used in the treatment of COVID-19 [ 1 , 2 ]. That is why supportive treatment, including supplementation of micronutrients such as vitamin C, has become a crucial part in management of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding COVID-19, based on molecular studies, it has been suggested that enhanced innate immune activation may promote a worse disease outcome [5]. However, most of our patients with AIDs are on colchicine treatment, and colchicine is one of the off-label medications used in the treatment of COVID-19, currently [18]. Gandol ni et al [19] have noted clinical improvement in their COVID-19 patient by using colchicine.…”
Section: Discussionmentioning
confidence: 99%